Landasan Filosofis-Teologis dalam Pengembangan Kurikulum PAI pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti Tingkat Sekolah Dasar - Bhima, Dhandy (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This study explores the philosophical and theological foundations in the development of the Islamic Religious Education (PAI) curriculum for elementary schools. The study aims to synthesize a holistic approach that integrates religious, moral, and academic dimensions to strengthen students' character and faith. The research methodology employed is a qualitative approach, utilizing an extensive literature review to analyze relevant principles in Islamic philosophy and theology. The study focuses on developing the PAI curriculum based on a philosophical-theological framework derived from the Qur'an and Hadith. The main findings indicate that integrating these foundations supports a comprehensive learning experience, which not only encourages students' moral development but also enhances their understanding of Islamic teachings. The results highlight the significant role of philosophical and theological foundations in shaping an educational environment aligned with religious and educational goals. Additionally, the study underscores the importance of continuous curriculum evaluation to ensure its relevance in addressing modern educational challenges. This research contributes to the literature on curriculum development by offering a framework applicable in various educational contexts while emphasizing a balanced approach to religious education.